Do asset pricing models explain sector returns on the Johannesburg Stock Exchange? - Ranchod, Ishani (University of the Witwatersrand, Johannesburg, 2024)
This study is conducted to evaluate whether style factors-based asset pricing models can explain sector returns on the Johannesburg Stock Exchange (JSE). The time frame for this research is between January 2007 to July 2023. Daily return data for both styles and sectors were used and calculated on a buy and hold basis with values that were obtained from Bloomberg and Iress. The methodology applied is a time-series regression used for a Gibbons- Ross-Shanken (1989) alpha test. This research provides investors with valuable insights into the specific asset pricing models and their underlying related style factors that can elucidate the cross-sectional variation of both sector and more comprehensively, share returns on the JSE. The results of the study confirm the effectiveness of various factor models in explaining sector returns on the JSE, with the six-factor model demonstrating superior performance. Notably, the six-factor model exhibits explanatory power for the financial and industrial sectors, highlighting its comprehensive ability to explain sector returns. The significance of size and value premiums across models underscores their importance in sector return analysis. Additionally, the six-factor model strengthens its ability to elucidate cross-sectional variation in styles and sector returns. Overall, the six-factor model emerges as a robust framework for analysing sector returns on the JSE, providing valuable insights into risk factors and how sectors perform.
A research report submitted in fulfillment of the requirements for the Masters of Commerce (Finance and Investments), In the Faculty of Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Asset; Pricing; Model; Sector; Return; Johannesburg; Exchange; SDG-8: Decent work and economic growth